Implementation of Religious Tolerance Values in Islamic Religious Education at a Public High School in Rembang - Moh Sholihuddin; Farida Isroani (FALASIFA : Jurnal Studi Keislaman, 2022)
The implementation ​​of religious tolerance is a standard of consideration consistent concept of humans towards mutual respect of other religions by living together without mixing beliefs. This research uses a qualitative case study approach through observation, interview and documentation. The results of the study show that: the values ​​of religious tolerance which are internalized in the subject of Islamic Religious Education at a public high school in Rembang have been well actualized by students and all school members through the realization of school programs that support the internalization of religious tolerance values. The supporting factor for the actualization of the value of tolerance at at a public high school in Rembang is the goal orientation of each school member, including the principles of wholeness, unity, humanism, and socialism.